THE EFFECTIVENESS OF HIGHER EDUCATION INSTITUTIONS IN TERMS OF GRADUATES EMPLOYMENT - Valery A. Gurtov; Evgeny A. Pitoukhin; Mikhail Y. Nasadkin (Высшее образование в России)
In this paper, we consider an approach to evaluating the HEI effectiveness in terms of graduate employment. Data source – the monitoring of graduates employment conducted by the Ministry of Education of Russian Federation. It is proposed to calculate the efficiency of graduates employment in view of the situation on the labor market expressed with an imbalance of supply and demand.